2017
DOI: 10.9734/ajrimps/2017/36744
|View full text |Cite
|
Sign up to set email alerts
|

Digital Imaging Analysis with Fractal Dimension in Oral Leukoplakia

Abstract: Introduction: Complex geometric structures can be quantified by fractal analysis by generating a fractal dimension (FD), thus it can also measure the complexity of mucosa such as oral leukoplakia and other potentially malignant disorders. Aim: The study was done to perform the fractal analysis (FA) of oral mucosa in Oral leukoplakia, and to calculate its fractal dimension. Materials and Methods: 10 patients with clinically and histopathologically confirmed oral leukoplakia are analyzed through FA using box cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…[ 26 ] Similarly, Uma Reddy et al . [ 27 ] conducted a research on pre and posttreated cases of oral leukoplakia and found a significant difference in FD in pre and post cases of Oral leukoplakia.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Similarly, Uma Reddy et al . [ 27 ] conducted a research on pre and posttreated cases of oral leukoplakia and found a significant difference in FD in pre and post cases of Oral leukoplakia.…”
Section: Discussionmentioning
confidence: 99%